2008
DOI: 10.1111/j.1365-2966.2008.14039.x
|View full text |Cite
|
Sign up to set email alerts
|

The clustering of radio galaxies atz≃ 0.55 from the 2SLAQ LRG survey

Abstract: We examine the clustering properties of low-power radio galaxies at redshift 0.4 < z < 0.8, using data from the 2SLAQ Luminous Red Galaxy (LRG) survey, and find that radio-detected LRGs (with typical optical luminosities of 3-5L * and 1.4 GHz radio powers in the range 10 24 -10 26 W Hz −1 ) are significantly more clustered than a matched population of radio-quiet ( 10 24 W Hz −1 ) LRGs with the same distribution in optical luminosity and colour.The measured scalelength of the two-point cross-correlation functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
101
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(128 citation statements)
references
References 47 publications
23
101
4
Order By: Relevance
“…Wake et al 2008;Mandelbaum et al 2009;Donoso et al 2010) have shown that radio-loud LRGs (analogous to LERGs) are in more massive haloes than non-radio galaxies of similar stellar mass, which is in agreement with our results on Σ5 and group fraction. Also in agreement with our work, Gendre et al (2013) use a sample of z < 0.3 radio galaxies to show that LERGs have denser average environments than HERGs, although there is no direct control for stellar mass in their work.…”
Section: The Role Of Halo Masssupporting
confidence: 93%
See 2 more Smart Citations
“…Wake et al 2008;Mandelbaum et al 2009;Donoso et al 2010) have shown that radio-loud LRGs (analogous to LERGs) are in more massive haloes than non-radio galaxies of similar stellar mass, which is in agreement with our results on Σ5 and group fraction. Also in agreement with our work, Gendre et al (2013) use a sample of z < 0.3 radio galaxies to show that LERGs have denser average environments than HERGs, although there is no direct control for stellar mass in their work.…”
Section: The Role Of Halo Masssupporting
confidence: 93%
“…In contrast, the environments of the HERGs and lower luminosity LERGs are indistinguishable from that of a matched control sample. Our results imply that high-luminosity LERGs lie in more massive haloes than non-radio galaxies of similar stellar mass and colour, in agreement with earlier studies (Wake et al 2008;Donoso et al 2010). When we control for the preference of LERGs to be found in groups, both high-and low-luminosity LERGs are found in higher-mass haloes (∼ 0.2 dex; at least 97 percent significant) than the non-radio control sample.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…In these samples, the typical 1.4 GHz radioluminosities for AGNs is 10 23 -10 26 W Hz −1 which is represen- Fig. 12: Different values for the real-space correlation length r 0 against redshift for RLQs and RQQs from SDSS DR5 (purple and gray downward triangles, Shen et al 2009), optical quasars (gray circles, Croom et al 2005;Ross et al 2009;Eftekharzadeh et al 2015), radio galaxies (dark green squares, Peacock & Nicholson 1991;Magliocchetti et al 2004;Wake et al 2008;Fine et al 2011;Lindsay et al 2014b), and FSRQs (orange star, Allevato et al 2014a) tative of FRI sources, whilst for our sample the average radioluminosity is ∼ 8 × 10 26 W Hz −1 , which is near the boundary between FRI and FRII sources.…”
Section: Clustering As a Function Of Redshiftmentioning
confidence: 99%
“…Studies of galaxies in groups and clusters by Best et al (2007) and Wake et al (2008) have shown that the environment of a radio galaxy has a significant effect on the radio emission. Sabater et al (2008Sabater et al ( , 2012 built on this result by comparing (a) the radio AGN activity in a sample of isolated galaxies (AMIGA sample; Verdes-Montenegro et al 2005) with that of a matched sample of galaxies in clusters (Miller & Owen 2001;Reddy & Yun 2004) The dependence of the redshift of the peak in space density (z peak ) on radio power for the best-fitting steep spectrum grid, showing that the numbers of the most powerful radio sources peak at the highest redshifts (Rigby et al 2011).…”
Section: Environmentmentioning
confidence: 99%